(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
In this work, I generalize the counter – example given by B – Alspach. And I find that there exists an infinity number of tournaments which is point – symmetric, but not rotation. [1]